Zad. 3
Wyłącz wspólny czynnik przed nawias :
a) 3x² + 3y² +3xy =
b) 0,3ab² - 0,9b² + 0,6ab =

zad. 4
Wykonaj mnożenie i przeprowadź redukcję wyrazów podobnych"
a) ½ab(8a-6ab+ab²-a² =
b) 4x(2xy-3xy²-5y)-2y(6x²+4x²y-10x)=


Liczę na szybką odp. :)

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-01T18:53:38+01:00
Zad 3
a) 3(x² + y² +xy)
b) 0,3b(b - 3b + 2a)

Zad 4
½ab(8a-6ab+ab²-a²) =
4a²b-3a²b+½a²b²-½a³b =
a²b+½a²b²-½a³b

4x(2xy-3xy²-5y)-2y(6x²+4x²y-10x)=
8x²y-12x²y² - 20xy -12x²y - 8x²y² + 20 xy =
- 4x²y-20x²y²
2010-03-01T18:57:38+01:00
Zad.3
a) 3(x²+y²+xy)
b) 0,3b(ab-3b+2a)
zad.4
a)4a²b-3a²b²+½a²b³-½a³b
b)8x²y-12x²y²-20xy-12x²y-8x²y²+20xy=-20x²y²-4x²y